Genetic and pharmacologic inhibition of ALDH1A3 as a treatment of β-cell failure - Son, Jinsook; Du, Wen; Esposito, Mark; Shariati, Kaavian; Ding, Hongxu; Kang, Yibin; Accili, Domenico (Nature communications, 2023)
Type 2 diabetes (T2D) is associated with β-cell dedifferentiation. Aldehyde dehydrogenase 1 isoform A3 (ALHD1A3) is a marker of β-cell dedifferentiation and correlates with T2D progression. However, it is unknown whether ALDH1A3 activity contributes to β-cell failure, and whether the decrease of ALDH1A3-positive β-cells (A+) following pair-feeding of diabetic animals is due to β-cell restoration. To tackle these questions, we (i) investigated the fate of A+ cells during pair-feeding by lineage-tracing, (ii) somatically ablated ALDH1A3 in diabetic β-cells, and (iii) used a novel selective ALDH1A3 inhibitor to treat diabetes. Lineage tracing and functional characterization show that A+ cells can be reconverted to functional, mature β-cells. Genetic or pharmacological inhibition of ALDH1A3 in diabetic mice lowers glycemia and increases insulin secretion. Characterization of β-cells following ALDH1A3 inhibition shows reactivation of differentiation as well as regeneration pathways. We conclude that ALDH1A3 inhibition offers a therapeutic strategy against β-cell dysfunction in diabetes. β-cell dedifferentiation is a key feature of type 2 diabetes. Here, the authors show evidence of re-differentiation of de-differentiated β-cells and identify ALDH1A3 as a key player in this process, proposing inhibition of ALDH1A3 as a treatment method for β-cell dysfunction in diabetes.